Pengembangan Kapasitas Kelembagaan dalam Meningkatkan Kewirausahaan Sosial Kelompok Tani di Kelurahan Kambaniru Kabupaten Sumba Timur - Saragih, Elsa Christin; Mbana, Febyningsi Rambu Ladu; Wadu, Junaedin; Ina, Yessy Tamu; Hana, Lince Tanggu; Andung, Evander Talu (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
The aim of the community service activity is in the form of counselling and training for the institutional capacity building of farmer groups in relation to increasing social entrepreneurship for the welfare of the members of the farmer group. The activity method used in this PkM is packaged using a workshop approach. The implementation of this PkM activity focuses on building institutional capacity and social entrepreneurship through counselling and training on group dynamics, institutional management & community development, training on farmer group administration and counselling and discussion on entrepreneurship social. Evaluation of activities is carried out by comparing the pre-test and post-test results of the implementation of all PKM activities. The average pre-test score was 49.2% and the post-test average score increased to 82.8%. This shows that there has been an increase in participants' knowledge about farmer group dynamics, institutional management and community development, bookkeeping and group administration, as well as knowledge about social entrepreneurship.